Is using a tooth brush safe? Successful endoscopic removal of adult tooth brush in two cases and short review - Krishnamurthy, Veeraraghavan; Kini, Ratnakar; Thangavel, Pugazhendhi; Mohammed, Kani Shaikh; K, Prem Kumar; Ali, Mohammed (International Journal of Research in Medical Sciences, 2017)
Ingestion of foreign bodies is common. However, ingestion of an adult tooth brush and its endoscopic removal is reported rare in literature. Here we report two cases of adult tooth brush ingestion with and without psychiatric illness in the past. Endoscopic removal of the tooth brush was done by using snare and rat tooth forceps differing from other case reports. Hence these cases are peculiar and reported.